Infectious Diseases of the Upper Gastrointestinal Tract - Min Roh; Yang Won Min (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2019)
Infectious diseases of the upper gastrointestinal tract are rare, but certain bacteria including Treponema pallidum and Mycobacterium tuberculosis may infect the esophagus, stomach, and duodenum even in an immunocompetent individual. Gastric syphilis is difficult to diagnose because it presents with non-specific symptoms and diverse endoscopic findings. Nevertheless, gastric syphilis should be considered in the differential diagnosis when a patient presents with chronic inflammatory gastric lesions such as multiple erosive/ulcerative lesions and stricture or with other evidence of syphilis. Histological evaluation and specific serological tests should be performed if syphilis is suspected. Esophageal and gastroduodenal tuberculosis also exhibits non-specific clinical manifestations. The diagnosis is confirmed by mucosal biopsy or aspiration cytology revealing the presence of caseating granulomata and/or acid-fast bacilli. Mycobacterial culture and polymerase chain reaction should be incorporated into routine diagnostic studies to improve the diagnostic sensitivity. The diagnosis of tuberculosis is occasionally confirmed indirectly by an excellent response of the patient to anti-tubercular therapy.